Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Produktivitas Kerja CV. Sukahati Pratama Tasikmalaya - Syahdila, Azrial Muhamad; Sutrisna, Arga; Wibawa, Gian Riksa (Utami Publisher, 2024)
This research was conducted with the aim of determining the influence of Organizational Culture and Work Environment on CV Work Productivity. Sukahati Pratama Tasikmalaya. The method used in this study is a quantitative method with a survey approach to primary data collection using the survey method. The survey method uses data obtained directly through a questionnaire distributed to 70 respondents who are employees of the CV.Sukahati Pratama Tasikmalaya Staff Management section. The technique used in this study is multiple linear regression analysis. Based on the results of the study, it can be seen that Organizational Culture and Work Environment simultaneously, have a significant effect on CV Work Productivity.Sukahati Pratama Tasikmalaya.Organizational Culture partially has a significant effect on CV Work Productivity. Sukahati Pratama Tasikmalaya, and the Work Environment partially have a significant effect on CV Work Productivity. Sukahati Pratama Tasikmalaya.